Differential Requirements for Mediator Complex Subunits in Drosophila melanogaster Host Defense Against Fungal and Bacterial Pathogens - Huang, Chuqin; Xu, Rui; Liégeois, Samuel; Chen, Di; Li, Zi; Ferrandon, Dominique (Frontiers in Immunology, 2021)
The humoral immune response to bacterial or fungal infections in Drosophila relies largely on a transcriptional response mediated by the Toll and Immune deficiency NF-κB pathways. Antimicrobial peptides are potent effectors of these pathways and allow the organism to attack invading pathogens. Dorsal-related Immune Factor (DIF), a transcription factor regulated by the Toll pathway, is required in the host defense against fungal and some Gram-positive bacterial infections. The Mediator complex is involved in the initiation of transcription of most RNA polymerase B (PolB)-dependent genes by forming a functional bridge between transcription factors bound to enhancer regions and the gene promoter region and then recruiting the PolB pre-initiation complex. Mediator is formed by several modules that each comprises several subunits. The Med17 subunit of the head module of Mediator has been shown to be required for the expression of Drosomycin, which encodes a potent antifungal peptide, by binding to DIF. Thus, Mediator is expected to mediate the host defense against pathogens controlled by the Toll pathway-dependent innate immune response. Here, we first focus on the Med31 subunit of the middle module of Mediator and find that it is required in host defense against Aspergillus fumigatus, Enterococcus faecalis, and injected but not topically-applied Metarhizium robertsii. Thus, host defense against M. robertsii requires Dif but not necessarily Med31 in the two distinct infection models. The induction of some Toll-pathway-dependent genes is decreased after a challenge of Med31 RNAi-silenced flies with either A. fumigatus or E. faecalis, while these flies exhibit normal phagocytosis and melanization. We have further tested most Mediator subunits using RNAi by monitoring their survival after challenges to several other microbial infections known to be fought off through DIF. We report that the host defense against specific pathogens involves a distinct set of Mediator subunits with only one subunit for C. glabrata or Erwinia carotovora carotovora, at least one for M. robertsii or a somewhat extended repertoire for A. fumigatus (at least eight subunits) and E. faecalis (eight subunits), with two subunits, Med6 and Med11 being required only against A. fumigatus. Med31 but not Med17 is required in fighting off injected M. robertsii conidia. Thus, the involvement of Mediator in Drosophila innate immunity is more complex than expected.